Multi‐wavelength Bragg coherent X‐ray diffraction imaging of Au particles. Issue 1 (27th January 2020) - Lauraux, F.; Cornelius, T. W.; Labat, S.; Richard, M.-I.; Leake, S. J.; Zhou, T.; Kovalenko, O.; Rabkin, E.; Schülli, T. U.; Thomas, O.
Abstract : Multi‐wavelength Bragg coherent X‐ray diffraction imaging is demonstrated on a single Au particle. The reconstructed Bragg electron density and phase field are in excellent agreement with the results obtained from conventional rocking scans of the same particle. Abstract : Multi‐wavelength (mw) Bragg coherent X‐ray diffraction imaging (BCDI) is demonstrated on a single Au particle. The multi‐wavelength Bragg diffraction patterns are inverted using conventional phase‐retrieval algorithms where the dilation of the effective pixel size of a pixelated 2D detector caused by the variation of the X‐ray beam energy is mitigated by interpolating the raw data. The reconstructed Bragg electron density and phase field are in excellent agreement with the results obtained from conventional rocking scans of the same particle. Voxel sizes of about 6 3  nm 3 are obtained for reconstructions from both approaches. Phase shifts as small as 0.41 rad, which correspond to displacements of 14 pm and translate into strain resolution better than 10 −4 in the Au particle, are resolved. The displacement field changes shape during the experiment, which is well reproduced by finite element method simulations considering an inhomogeneous strained carbon layer deposited on the Au particle over the course of the measurements. These experiments thus demonstrate the very high sensitivity of BCDI and mw‐BCDI to strain induced by contaminations. Furthermore, mw‐BCDI offers new opportunities for in situ and operando 3D strain imaging in complex sample environments.